Numerical Analysis of Concrete Gravity Dam Seepage Characteristics Evolution considering the Calcium Leaching Effect - Kailai Zhang; Liqun Xu; Liting Qiu; Jiacheng Tan; Chao Yang; Kai Zhang (Advances in Civil Engineering)
During the long-term service life of hydraulic structures, the calcium compounds in cement-based materials decompose in the aqueous environment, leading to the continuous change of seepage characteristics. To study the influence of calcium leaching on the concrete dam seepage characteristics, we proposed a new mathematic model of the cement-based material calcium leaching model under advection-diffusion-driven leaching. A solid-liquid nonequilibrium model is adopted to model the decomposition of calcium hydroxide (CH) and calcium silicate hydrate gel (C-S-H). To calculate the porosity more accurately, the proposed model takes the effect of different calcium compound decomposition on the porosity increase in consideration, respectively. Shimantan dam is selected for the three-dimensional (3D) calcium leaching analyses. The 3D finite element model of this dam is analyzed using COMSOL Multiphysics software that is based on the finite element method. Based on the proposed model, seepage characteristics evolutions of the Shimantan dam are studied. Good agreement between the numerical results and the monitored data indicates the accuracy of this simulation. The result shows that after 100 a leaching duration, the uplift pressure increases by 40.8%, and the leakage quantities of the dam body and foundation increase by 48 and 17 times. The rise of uplift pressure and leakage changes caused by curtain deterioration are the main influences of calcium leaching on the dam seepage. The parameter sensitivity results show that it is necessary to reduce CH content in cement-based materials to obtain better calcium leaching durability. This model and simulation results can guide the operation of concrete dams under advection-diffusion-driven leaching.